EDM wire cut machine - Seow, Zhen Jie; Gan, Yan Nee; Long, Mei Mei; Cheong, Soo Thing; Rajemi, Mohamad Farizal (2013)
Electrical discharge machining (EDM) is a metal machining process that typically used for machining hard metals.EDM tool discharges thousands of electrical sparks to the conductive metal in machining it.This research discussed the concept and operation of wire cut EDM.The results reveal the advantages and disadvantages of using wire cut EDM in machining a spur gear.Although the EDM wire cut may require higher investment compared to other type of machining, it is still the most preferred machining technology in the heavy manufacturing industries.